Seasonal variability of ocean circulation near the Dotson Ice Shelf, Antarctica - Yang, H. W.; Kim, T.-W.; Dutrieux, Pierre; Wåhlin, A. K.; Jenkins, Adrian; Ha, H. K.; Kim, C. S.; Cho, K.-H.; Park, T.; Lee, S. H.; Cho, Y.-K. (Nature Communications, 2022)
Recent rapid thinning of West Antarctic ice shelves are believed to be caused by intrusions of warm deep water that induce basal melting and seaward meltwater export. This study uses data from three bottom-mounted mooring arrays to show seasonal variability and local forcing for the currents moving into and out of the Dotson ice shelf cavity. A southward flow of warm, salty water had maximum current velocities along the eastern channel slope, while northward outflows of freshened ice shelf meltwater spread at intermediate depth above the western slope. The inflow correlated with the local ocean surface stress curl. At the western slope, meltwater outflows followed the warm influx along the eastern slope with a ~2–3 month delay. Ocean circulation near Dotson Ice Shelf, affected by sea ice distribution and wind, appears to significantly control the inflow of warm water and subsequent ice shelf melting on seasonal time-scales.